Phonological and Grammatical Errors in Arabic Speaking Skills: Insights from Female Banjar Learners of Islamic Boarding School - Habib, Moh. Tohiri; Sari, Alvia Putri Prima; Amini, Nurul; Wahyudi, Iqmal (AL-TA'RIB : Jurnal Ilmiah Program Studi Pendidikan Bahasa Arab IAIN Palangka Raya, 2025)
Mastering a foreign language requires not only memorization but also overcoming deeply ingrained linguistic habits. For Banjar learners studying Arabic, phonological and grammatical challenges pose significant barriers to fluency. This study explores the phonological and grammatical errors encountered by Banjar learners in Arabic speaking skills at Pesantren Darullughah Wadda'wah Putri. Through a qualitative descriptive approach, it identifies the prevalent types of errors, their underlying causes, and potential pedagogical strategies for improvement. The findings reveal significant phonological issues, including substitutions of Arabic phonemes influenced by the Banjar dialect, as well as grammatical inconsistencies due to overgeneralization and limited exposure to authentic Arabic structures. The study highlights native language interference, lack of phonetic training, and psychological barriers, such as fear of criticism, as primary causes of these challenges. Proposed solutions include intensive phonetic drills, immersive language environments, context-based grammar instruction, and the integration of cultural and technological resources. This research contributes to Arabic language pedagogy by providing targeted strategies to enhance the proficiency of Banjar learners, bridging linguistic gaps while respecting their cultural identity.